Mykyta Shapoval as a leader of the Ukrainian emigration in interwar Czechoslovakia. - Savchenko, Angela (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2023)
The purpose of the article. On the basis of historical sources and archival materials, highlight the activities of Mykyta Shapoval as a leader of Ukrainian emigration in Czechoslovakia in the period 1921-1932, analyze his role and significance in the foundation and development of Ukrainian educational, scientific, and cultural institutions in the Czechoslovak SSR.The research methodology. Methods of analysis and synthesis, cause-and-effect relationships were used, principles of objectivity were applied.The scientific novelty. On the example of the figure of Mykyta Shapoval, for the first time, the problem of the role of the individual, leadership in the organization of full-fledged life activities of the Ukrainian community in emigration, provision of its basic educational, cultural, household, sports development and medical services, the issue of political unity and cohesion in the Ukrainian community in the conditions of forced resettlement to Czechoslovakia.Conclusions. During the interwar period, the Ukrainian emigration in Czechoslovakia was able to preserve and realize itself as a powerful national center with Ukrainian educational, scientific, cultural institutions and institutions, preserve its own national identity, develop independently, and also make its contribution to the development of the cities and towns of Czechoslovakia, which became instead of its compact settlement. Such a high result is to a large extent the personal merit of Mykyta Shapoval and the Ukrainian Public Committee created on his initiative.